2014
DOI: 10.1016/j.gene.2014.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-regulated protein 78 may play a crucial role in promoting the pulmonary microvascular remodeling in a rat model of hepatopulmonary syndrome

Abstract: Objective This study is to investigate the role of glucose-regulated protein 78 (GRP78) in the pulmonary microvascular remodeling during hepatopulmonary syndrome (HPS) development. Methods The rat models with liver cirrhosis and HPS were induced by multiple pathogenic factors for 4 to 8 wk. The concentrations of alanine transferase (ALT) and endotoxin in plasma were detected in the models, followed by the detection of GRP78 expression. RT-PCR, quantitative real-time PCR and Western blotting were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…These data showed increased expression levels of VEGF, factor VIII-related antigen and GRP78 and decreased levels of anti-apoptotic proteins (52). These results led to the assumption that GRP78 may play a role in inducing pulmonary vascular remodelling in HPS through promoting cell proliferation and survival and inhibiting apoptosis (52). Figure 2 summarizes the current knowledge on the pathogenesis and pathophysiology of HPS based on rat studies.…”
Section: Angiogenesismentioning
confidence: 92%
See 2 more Smart Citations
“…These data showed increased expression levels of VEGF, factor VIII-related antigen and GRP78 and decreased levels of anti-apoptotic proteins (52). These results led to the assumption that GRP78 may play a role in inducing pulmonary vascular remodelling in HPS through promoting cell proliferation and survival and inhibiting apoptosis (52). Figure 2 summarizes the current knowledge on the pathogenesis and pathophysiology of HPS based on rat studies.…”
Section: Angiogenesismentioning
confidence: 92%
“…A recent study investigated the role of glucose‐regulated protein 78 (GRP78) in the pulmonary microvascular remodelling during experimental HPS development . These data showed increased expression levels of VEGF, factor VIII‐related antigen and GRP78 and decreased levels of anti‐apoptotic proteins .…”
Section: Hepatopulmonary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…17 Many data have shown that GRP78 is overexpressed on the cell surface in many human cancers such as melanoma, lung cancer, breast cancer, and hepatocellular carcinoma. [18][19][20] Cell surface GRP78 is involved in the regulation …”
Section: Introductionmentioning
confidence: 99%
“…First, pulmonary angiogenesis and vascular remodeling are considered key pathogenic features of HPS [ 3 , 30 ], mostly involving the activation of vascular endothelial growth factor (VEGF)-dependent pathways [ 14 , 31 33 ]. In this context, it is of note that some of the top differentially methylated genes identified in patients with HPS ( Table 2 ) were also related to angiogenesis, including VAV3 [ 34 ], PAX 8 [ 35 ], K-RAS [ 36 ] and LAMA2 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%